Memories of the Present : A Collection of Holiday Recipes, Crafts, Customs, and Helpful Miscellany - Edited by Fullington, William N. (US Visconsi & Jacobs, 1989)
Includes Christmas songs, stories, crafts, and recipes.
Include Color Illustration
Keywords: Christmas -- Handicraft